2013
DOI: 10.1021/jm4005219
|View full text |Cite
|
Sign up to set email alerts
|

Bivalent Ligands That Target μ Opioid (MOP) and Cannabinoid1 (CB1) Receptors Are Potent Analgesics Devoid of Tolerance

Abstract: Given that mu opioid (MOP) and canabinoid (CB1) receptors are co-localized in various regions of the CNS and have been reported to associate as heteromer (MOP-CB1) in cultured cells has raised the possibility of functional, endogenous MOP-CB1 in nociception and other pharmacologic effects. As a first step in investigating this possibility, we have synthesized a series of bivalent ligands 1-5 that contain both mu agonist and CB1 antagonist pharmacophores for use as tools to study the functional interaction betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 50 publications
1
58
0
Order By: Relevance
“…With the exception of 8a – 8c and 11d – 11f , the intermediates 7 – 12 have been reported previously by us. 8, 18, 19, 47 Using literature procedures, 46 the amine 8a was prepared and converted into 8c . Calcium mobilization studies in CCR 5 expressing HEK cells stimulated by CCL 5 revealed that 8c was equally potent at inhibiting calcium release (Supplementary Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…With the exception of 8a – 8c and 11d – 11f , the intermediates 7 – 12 have been reported previously by us. 8, 18, 19, 47 Using literature procedures, 46 the amine 8a was prepared and converted into 8c . Calcium mobilization studies in CCR 5 expressing HEK cells stimulated by CCL 5 revealed that 8c was equally potent at inhibiting calcium release (Supplementary Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, several lines of evidence suggest that cannabinoid and dopamine signalling pathways exhibit cross-talk with mu-opioid receptors. Firstly, there is co-localisation between CB1 cannabinoid receptors and mu-opioid receptors in the rat striatum and CB1 receptors have been shown to associate with mu-opioid receptors in transfected HEK293 cells (Rodriguez et al, 2001;Le Naour et al, 2013). Secondly, the reinforcing or rewarding effects of mu-opioid receptor ligands are reduced in CB1 knockout mice, and vice versa (Martin et al, 2000;Cossu et al, 2001;Ghozland et al, 2002).…”
Section: Potential Mechanisms Underlying Diet-induced Changes In Mu-omentioning
confidence: 99%
“…170172 A combination of mu-receptor agonists and cannabinoid receptor agonists in rhesus monkey models, showed significant antinociception. 173 Mu opioid receptor and CB1 (cannabinoid) receptor heterodimers 174 and mu-mGluR5 175,176 heteromers with opioid and non-opioid binding sites, expressed strong antinociceptive effects in a range of models. In addition, a small molecule agonist for the mu-kappa opioid receptor heteromer, NNTA, is a potent antinociceptive agent with no propensity to display physical dependence or drug-seeking behavior.…”
Section: Survey Of Current Targets Of Pain Therapeuticsmentioning
confidence: 99%